Dental status of young adults born with very low birthweight: A national cohort study. Issue 3 (29th November 2020) - McKelvey, Victoria; Darlow, Brian A.; Horwood, L. John; Martin, Julia
Abstract: Objectives: Little is known about the oral health of very low birthweight (<1500 g: VLBW) young adults. This study compared the oral health and self‐reported oral health in a 1986 birth cohort of VLBW young adults with that of term‐born controls. Methods: Oral health interviews and dental examinations were conducted. The dental examinations were carried out in a dental clinic using the standardized examination protocols from the 2009 New Zealand Oral Health Survey. Participants were interviewed to obtain data on self‐reported oral health, oral hygiene practices, use of dental health services and oral health–related quality of life using the OHIP‐14 measure. Results: Interviews were completed by 250 VLBW participants and 226 (90.4%) of those underwent the dental examination. All 100 controls completed both the interview and dental examination. While there were few overall differences in clinical or self‐reported oral health between the VLBW or control groups, proportionally fewer VLBW participants attended the dentist for regular check‐ups or cleaned between their teeth than controls. The VLBW and controls did not differ in the prevalence of untreated dental caries or in the number of carious tooth surfaces after adjusting for confounders. However, participants in the control group had more teeth that had been restored due to caries (4.4 teeth) than did the VLBW group (3.4 teeth, P  = .045), after adjusting for confounding. Conclusions: Very low birthweight young adults showed poorer self‐care than the control group when it came to oral health; they were less likely to regularly attend dental visits, had poorer oral hygiene and were less likely to have had their dental disease treated. VLBW young adults should be encouraged to attend regular dental check‐up appointments and to carry out effective home oral hygiene care.